2010
DOI: 10.1074/jbc.m109.092569
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Isochorismate-derived 2,3-Dihydroxybenzoic 3-O-β-d-Xyloside in Arabidopsis Resistance to Pathogens and Ageing of Leaves

Abstract: An intricate network of hormone signals regulates plant development and responses to biotic and abiotic stress. Salicylic acid (SA), derived from the shikimate/isochorismate pathway, is a key hormone in resistance to biotrophic pathogens. Several SA derivatives and associated modifying enzymes have been identified and implicated in the storage and channeling of benzoic acid intermediates or as bioactive molecules. However, the range and modes of action of SA-related metabolites remain elusive. In Arabidopsis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(104 citation statements)
references
References 70 publications
6
98
0
Order By: Relevance
“…This analysis confirmed that they are DHBA glycosides and revealed that the sugar moiety is b-D-xylose in both compounds 3 and 4. The 1 H and 13 C NMR spectra of compounds 3 and 4 agreed with those previously described for 2,5-DHBA 5-O-b-D-xyloside (2,5-DHBAX) and 2,3-DHBA 3-O-b-D-xyloside (2,3-DHBAX), respectively ( Figure 3C; Table S1) (Fayos et al 2006;Bartsch et al 2010). We reexamined Col-0 by more sensitive methods and were able to detect 2,5-DHBAX using fluorescence detection or LC-MS, although the level of this compound was below the detection limit of the UV detector used in our initial HPLC profiling experiments (data not shown).…”
Section: Identification Of Four Dhba Glycosides From Arabidopsissupporting
confidence: 69%
See 2 more Smart Citations
“…This analysis confirmed that they are DHBA glycosides and revealed that the sugar moiety is b-D-xylose in both compounds 3 and 4. The 1 H and 13 C NMR spectra of compounds 3 and 4 agreed with those previously described for 2,5-DHBA 5-O-b-D-xyloside (2,5-DHBAX) and 2,3-DHBA 3-O-b-D-xyloside (2,3-DHBAX), respectively ( Figure 3C; Table S1) (Fayos et al 2006;Bartsch et al 2010). We reexamined Col-0 by more sensitive methods and were able to detect 2,5-DHBAX using fluorescence detection or LC-MS, although the level of this compound was below the detection limit of the UV detector used in our initial HPLC profiling experiments (data not shown).…”
Section: Identification Of Four Dhba Glycosides From Arabidopsissupporting
confidence: 69%
“…Feeding experiments using isotope-labeled SA demonstrated that 2,5-DHBA and 2,3-DHBA could be made from SA in leaves of various plants including Arabidopsis (Ibrahim and Towers 1959;Bartsch et al 2010). Consistent with this observation, Arabidopsis isochorismate synthase mutant sid2, which is defective in SA biosynthesis, was found to be deficient in DHBA glycosides (Bartsch et al 2010).…”
Section: Figuresupporting
confidence: 64%
See 1 more Smart Citation
“…Other SNP loci like B440 may encode regulatory proteins (Fan et al., 2016; Sawaki et al., 2009), which similarly respond to stress by regulating transcription of genes involved in pathways such as immunity response. Biomarker M435T576 and its related metabolites belong to a class of terpenoid derivatives that have known antimicrobial and antifungal properties (Bartsch et al., 2010; Chang, Xuan, Xu, & Zhang, 2001; Meng, Lu, Li, Yang, & Tan, 1999; Whitehead, Tiramani, & Bowers, 2016) and are likely sensitive to disease‐mediated signaling processes (Caplan, Padmanabhan, & Dinesh‐Kumar, 2008). For instance, M227T630 was identified as Cornolactone C, an iridoid isolated previously from C. florida (He et al., 2014), which belongs to a compound class known to accumulate in response to infection and has documented antimicrobial properties (Marak, Biere, & Van Damme, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…S3). SAG might serve as a storage form of SA, whereas DHBA, which has a weak PR-1-inducing activity (Bartsch et al, 2010), is likely to be the activemetabolite. Expression of PR-1 was partially reduced in dde2-2 and even further compromised in coi1-t (Fig.…”
Section: Coi1 In the Roots Influences The Disease Phenotype Of The Shootmentioning
confidence: 99%